Distributed Text Services (DTS): A Community-Built API to Publish and Consume Text Collections as Linked Data - Bridget Almas; Hugh Cayless; Thibault Clérice; Vincent Jolivet; Pietro Maria Liuzzo; Jonathan Robie; Matteo Romanello; Ian Scott (Journal of the Text Encoding Initiative)
This paper presents the Distributed Text Service (DTS) API Specification, a community-built effort to facilitate the publication and consumption of texts and their structures as Linked Data. DTS was designed to be as generic as possible, providing simple operations for navigating collections, navigating within a text, and retrieving textual content. While the DTS API uses JSON-LD as the serialization format for non-textual data (e.g., descriptive metadata), TEI XML was chosen as the minimum required format for textual data served by the API in order to guarantee the interoperability of data published by DTS-compliant repositories. This paper describes the DTS API specifications by means of real-world examples, discusses the key design choices that were made, and concludes by providing a list of existing repositories and libraries that support DTS.